THE MARGINALIZING EFFECTS OF HETERONORMATIVITY IN THE BOYS IN THE BAND (Revista Apotheke, 2021)
The study contributes to a better understanding of the cultural history of masculinity and sexuality. To do so, it takes as a basis Mart Crowley's play The boys in the band, their respective American staging (1968-2018) and their film version (2020) to print discussions about pre-Stonewall, pré-fechação, pré-lacração. The authors, following the impressions of Tony Adams (2011), take into account the central role that the exit from the closet - the male homosexual secret - plays in Western culture, but moving away from the dualistic logic, which forces the subject to leave or remain in the closet, allowing him to glimpse the politics of identity as always open, continuous, and never totally stable.
Keywords: The boys in the band; gay theater; closet culutre